FERTILIZANTES FOLIARES, REGULADOR DE CRESCIMENTO E GLYPHOSATE NO CRESCIMENTO VEGETATIVO DA SOJA TOLERANTE AO GLYPHOSATE (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The present work has the objective of measure the performance of the soybean submitted to doses of glyphosate, as well as the association of products to the herbicide, aiming the process of reversion of the phytotoxic effect in soybean RR2. The experiment was conducted in November of 2015 to January of 2016, in a greenhouse at the Federal University of Paraná - Palotina Sector. The cultivar was a Monsoy 6210 IPRO® in a completely randomized design with four replicates. Plants were submitted to the herbicide glyphosate in a dose of 0, 720, 1440, 2160 and 2880 g a.e. ha -1 and doses of glyphosate in combination with the products growth regulator, in a dose of 250ml ha-1,manganese and a aminoacids compound (1L ha-1) Plant chlorophyll index, dry matter of roots and aerial part, and visual note of phytotoxicity was evalueted, which was determined by assigning notes representing a percentage of damaged leaf area. The data were submitted to a variance analysis and a test of rate comparation was used (Tukey) and were submitted to a linear regression test for the dose test (p≤0.05). It was observed that in the cultivar adopted, in its circumstances of this experiment, the manganese and the growth regulator were effective in the evaluation of the visual note of phytointoxication. In dry mass of roots and aerial part there was no significant difference between treatments.